SAT-289 An Unusual Virilizing Ovarian Tumor in Adolescence - Force, Bahar (J Endocr Soc, 2019)
Background: The etiology of hyperandrogenism in adolescent females includes polycystic ovarian syndrome, non-classical congenital adrenal hyperplasia (CAH), Cushing’s syndrome, androgen-secreting tumors (adrenal or ovarian) or exogenous use. Ovarian tumors producing androgens comprise <5% of all ovarian neoplasms and usually originate from sex cord stromal cells. There are sporadic case reports of mature cystic teratomas (MCTs), a type of germ cell tumor, causing hyperandrogenism in women but only two reported cases of virilizing MCTs in adolescent girls (1, 2). We present a third case of this nature. Case presentation: A 17-year old girl with no past medical history presented with worsening abdominal distension and discomfort. She was also noted to have excessive thick facial hair which she stated had been present throughout adolescence. She reported recent irregularity in her menstrual periods. She had no history genital abnormalities at birth or premature adrenarche, thelarche or menarche. She denied using anabolic steroids or other medications. Family history was negative for CAH or sudden infant death. On examination, there was significant abdominal distension, terminal hair over the chin, upper lip, side-burns and abdomen, as well as severe clitoromegaly with prominent glans measuring 3cm x 1.5cm, but no evidence of acanthosis nigricans. Chemistry showed testosterone of 178.3 ng/dL (3.75 - 49.57 ng/dL), DHEA-S of 550.4 mcg/dL (150.0 - 590.0 mcg/dL) and 17-hydroxyprogesterone of 224.7 ng/dL (26 - 325 ng/dL). Her abdomino-pelvic ultrasound and CT scan showed a 35.5 cm cystic mass with focal fatty components and dystrophic calcifications suggestive of MCT. Adrenal glands were normal. The patient underwent an exploratory laparotomy with left salpingo-oopherectomy and right cystectomy. Preliminary pathology results showed bilateral MCTs. Two weeks post-operatively, testosterone level decreased to 32.5 ng/dL. Conclusion: Given the normalization of testosterone after surgery, the bilateral MCTs are the suspected source of the patient’s androgen excess. MCTs are the most common ovarian neoplasm in adolescent females, but they are an exceedingly rare cause of hyperandrogenemia. They can be slow-growing and local manifestations may not present until years later. However, testosterone-secreting MCTs may be brought to a physician’s attention due to signs of virilization. A multidisciplinary approach with primary care physicians, endocrinologists, gynecologists and pathologists is needed to make an accurate diagnosis in a timely manner. References: 1. Hoffman JG et al Virilizing ovarian dermoid cyst with leydig cells. J Pediatr Adolesc Gynecol. 2009;22:e39-40. 2. Rotenberg, O. et al (2009) Testosterone-secreting mature ovarian teratoma causing severe virilization in an adolescent: sonographic and color Doppler characteristics. J. Ultrasound Med., 28, 85-88.